Appendicitis and uterine abscess: presentation of an unusual fistula between the gynaecological and gastrointestinal tracts. (14th September 2012) - Parsons, Sian Ruth; Bennett, Joanne Elizabeth; Kaloo, Philip; Scott, Mike
Abstract : The authors present the case of a 65-year-old woman with clinical and radiological evidence of pelvic sepsis and a medical history of endometrial ablation 20 years previously. She underwent laparotomy after failing to settle with a course of intravenous antibiotics and her appendix was found to have perforated into the uterus with abscess formation which had not discharged vaginally presumably due to widespread intrauterine synechia following her endometrial ablation. She underwent appendectomy and hysterectomy and made a full recovery with no complications. Macroscopic and microscopic examination suggested the appearances are those of an abscess of the uterine fundus with part of the appendix incorporating into the abscess mass.